THE REPRESENTATION OF THE FEMALE GAZE IN THE RELIGIOUS HORROR FILM QODRAT 2 - Dewi Sulistia Wati (Universitas Islam Negeri Mataram, 2026)
This study examines the representation of the female gaze in female characters in the Indonesian religious horror film Qodrat 2 (2025). The position of women in Indonesian horror cinema is framed in a patriarchal manner. The purpose of this study is to identify the semiotic aspects of the female gaze as an active counter-discourse within the religious horror genre, using qualitative methods grounded in Roland Barthes’s semiotic approach. The findings show that the film Qodrat 2 consistently reposition Azizah from a passive trauma victim to an active subject across six interrelated scenes that support her rise from adversity, economic independence, emotional complexity, social participation, agency in the face of threats, and autonomous spiritual resistance.